Eksperimen Listrik Searah (DC) pada Power Bank Sederhana Menggunakan Simulasi PhET - Erlida Amnie; Berkibra Lumbantoruan (Universitas Garut, 2026)
The research is aim to determine the use of PhET simulation in physics learning on direct current (DC) electrical circuits through the design and analysis of a simple power bank with the help of PhET simulation. The experiment was conducted using the Circuit Construction Kit: DC module to build a circuit consisting of an electrical power source (battery), a load (resistor), a switch, and a current and voltage measuring instrument. With variations in resistance values, the relationship between voltage, current, and resistance was observed based on Ohm's Law. Through this activity, students can understand the basic concepts of direct current, electrical measurements, and the simple working principle of a power bank. PhET simulation has proven effective as an interactive learning medium because it facilitates visualization of current flow and helps analyze results without the need for physical laboratory equipment. Keywords: DC, power bank,, Ohm law, PhET, interractive learning